Wild animals : explore the fascinating worlds of-- - 20160731 frey50; McGee, John F.; Feeney, Kathy, 1954-; Feeney, Kathy, 1954-; McPherson, Winnie, 1930-; Fredericks, Anthony D. (Minnetonka, Minn. : NorthWord Press, 2000)
Describes the habitat, appearance, food, and behavior of four threatened or endangered animals.
Pandas / by Kathy Feeney -- Cheetahs / by Winnie MacPherson -- Elephants / by Anthony D. Fredericks -- Koalas / by Kathy Feeney.
Keywords: Giant panda; Cheetah; Elephants; Koala; Endangered species